- ANALISIS EFEKTIVITAS KELEMBAGAAN HUTAN ADAT DI KABUPATEN MUARA BUNGO PROVINSI JAMBI (STUDI KASUS PADA HUTAN ADAT BATU KERBAU): Perhutanan sosial, Hutan Adat Batu Kerbau, Kelembagaan - Fazriyas Fazriyas; Ahmad Muzakkir muzakkir; Maria ulfa ulfa; Rahmad Nurmansah Rahmad; Ahyauddin Ahyauddin; agung kurnia agung (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2025)
Customary forests are one of the social forestry program schemes in Indonesia that provide legal access to local communities in forest management by strengthening the local wisdom of customary law communities. The research location is in the Batu Kerbau (buffalo stone) customary forest, Muara Bungo Regency, Jambi Province. The Batu Kerbau customary forest is the first forest formed in Muaro Bungo Regency in 2002. The purpose of this study was to determine the effectiveness of customary forest institutions in the management of the Batu Kerbau customary forest. The level of institutional effectiveness of the Batu Kerbau customary forest uses 8 (eight) criteria according to Ostrom (1990). Sampling of respondents was carried out using purposive sampling method so that 25 informants were obtained. Quantitative data analysis is based on the results of filling out the questionnaire which is then analyzed using a Likert Scale and for qualitative data obtained from interviews and descriptions to strengthen the results of quantitative data. The results of the study show that the level of effectiveness of the Batu Kerbau customary forest institution is classified as moderate for the level of existence or existence of customary forest with a percentage score of 61.80%. Some of these factors are divided into 2 factors, namely driving factors and inhibiting factors. The driving factor is in the form of clearly identified boundaries and strict sanctions in accordance with the level of guilt. The weakness factor is that the contribution of customary forests from the economic aspect to the livelihood structure of the Batu Kerbau Keywords : Social forestry, Batu Kerbau customary forest, institutional